Developing a Virtual Nature Laboratory of Faculty Social Science (LAV-FIS) to Assists Field-Based Learning during Pandemic: A Need Analysis Review - Kurniawan, Bayu; Shrestha, Rajendra Prasad; Astina, I Komang; Hadi, Nur; Irawan, Listyo Yudha; Kurniawati, Elya; Wiradimadja, Agung (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The Covid-19 outbreak has affected several aspects of field-based learning. The best way to ensure the survival and safety of everyone involved in field-based learning is to adapt and integrate technology. In response to this problem, numerous innovations in learning technology that lead to the virtualization of the learning environment have begun to emerge. However, the various application products developed have fallen short of the expectations of students. As a result, in order to design the optimal virtual application for use in field-based learning, a needs analysis must be done. This study offers an understanding of student needs for virtual field-based learning applications. An online survey of 140 active university students was carried out to do so. The results showed that students require applications with sophisticated features that resemble the real world for the implementation of online field-based learning. They expect the incorporation of online meeting features, 360 Virtual Reality Panorama, access to learning videos, augmented reality, learning materials, chatbox, and multimedia into the software that will be developed.